Knowledge of Women on Early Symptoms of Cancer in Rural and Urban Areas of Mangalore - Jacob, Sonia; D'Silva, Fatima (Journal of Health and Allied Sciences NU, 2012)
A descriptive cross sectional survey design was adopted for the study to assess and compare the level of knowledge of women on early symptoms of cancer. The sample consisted of 200 women, 100 from urban area of Jeppu and 100 from rural area of Natekal PHC. Stratified Sampling technique was used for selection of the samples. The data was collected by a demographic pro forma and a knowledge questionnaire which consisted of 23 multiple choice and 11 dichotomous (Yes/No) questions.Reliability of the tool was assessed using split half method and the reliability coefficient was found to be 0.9.Though the overall knowledge score of urban women was comparatively higher (38.26) than their rural counterparts (34.79), It was encouraging to note that rural women (53.6%) had better knowledge regarding risk factors and etiology of cancer when compared to urban women (51.02%).In India cancer related mortality is very high due to lack of awareness of the early symptoms leading to delayed screening and increased exposure rate of the risk factors. Nurses play a significant role in the disease prevention and health promotion of patients with cancer. Educational programs on healthful living with cost effective and motivating teaching strategies can be undertaken for the community so as to curb the mortality and morbidity associated with cancer
Keywords: Knowledge; Women; Early symptoms of cancer